The Media Poetry of Nikolai Rubtsov in the Internet Poetic Discourse of the 21st Century - Bejenaru, L. ("Акад. Е.А. Бөкетов ат. Қарағанды ун-ті" КЕАҚ баспасы, 2023)
This article considers the problems of Internet discourse and media space itself as one of the main characteristics of Internet discourse. The characteristics of media texts, an important product of media space, are analyzed. The necessity of studying media-poetry, which is a synthesis of poetry and various media spaces, is revealed and justified. The author uses the creative work of the famous Russian poet N. Rubtsov as an example. On the basis of the research, the author proves that Nikolai Rubtsov is the most sought-after Russian poet on the Russian-language Internet. The author argues that media-poetry in the XXI century poetic Internet discourse gives the poet's work a postmodern sounding. The urgency of the article lies in the fact that the study of the language of the Internet is in its infancy; so far few works have been devoted to the subject. The study of the Internet language is promising and has a number of aspects which are waiting for their researchers.
ХХІ ғасырдағы поэтикалық интернет-дискурстағы Николай Рубцовтың медиапоэзиясы
Медиапоэзия Николая Рубцова в поэтическом интернет-дискурсе XXI века
Keywords: media poetry; Internet poetic discourse; Nikolai Rubtsov; media space; media text